Recent Advances in Bioengineered Scaffolds for Cutaneous Wound Healing - Qin, Jianghui; Chen, Fang; Wu, Pingli; Sun, Guoming (Frontiers in Bioengineering and Biotechnology, 2022)
Wound healing is an evolved dynamic biological process. Though many research and clinical approaches have been explored to restore damaged or diseased skin, the current treatment for deep cutaneous injuries is far from being perfect, and the ideal regenerative therapy remains a significant challenge. Of all treatments, bioengineered scaffolds play a key role and represent great progress in wound repair and skin regeneration. In this review, we focus on the latest advancement in biomaterial scaffolds for wound healing. We discuss the emerging philosophy of designing biomaterial scaffolds, followed by precursor development. We pay particular attention to the therapeutic interventions of bioengineered scaffolds for cutaneous wound healing, and their dual effects while conjugating with bioactive molecules, stem cells, and even immunomodulation. As we review the advancement and the challenges of the current strategies, we also discuss the prospects of scaffold development for wound healing.